PENGETAHUAN REMAJA PUTRI TENTANG KEHAMILAN,DI WILAYAH KERJA PUSKESMAS KLUNGKUNG I, BALI TAHUN 2014 - Ellen Kwesley (DiscoverSys Inc., 2016)
The increasing incidence of pregnancies in young girls from year to year will cause health and social issues for teenagers themselves. Since 2010, the number of visits of pregnant women aged <20 years old in Puskesmas Klungkung I constantly increasing. This study purposes to know the knowledge of the young women about early pregnancy in Klungkung I Primary Health Care. Study used a qualitative descriptive research design. Samples were selected purposively. Data were collected by in-depth interviews. Analysis of data using thematic analysis method. Research conducted at Klungkung I Primary Health Care on August 7 to September 6, 2014. Total of 6 respondents engaged in research with the characteristics of education are diverse, 1 respondentis still unmarried and 3 respondents are married while pregnant. The results showed knowledge of the young women about pregnancy affect sexual behavior before marriage. Knowledge of respondents about pregnancy is still somewhat less so the respondents did not know the impact of early pregnancy and did not know about the prevention of pregnancy. So the promotion of reproductive health should be more intense, so that teens can get accurate information.Â